BARRIERS AND DRIVERS TO SPEED UP PREFABRICATED HOUSING IN MALAYSIAN HOUSING PROJECTS - Ahmad, Abd Jalil; Azlan Raofuddin, Nuruddin; Mastura, Jaafar; Md Azree, Othuman Mydin (Penerbit Universiti Sains Malaysia, 2017)
Providing adequate proper housing is one of the Malaysian government agenda towards becoming a develop nation in the year 2020. Under Construction Industry Transformation Plan (CITP) launched in 2015, the government aims to provide enough and comfortable housing to all citizen, and achieve a new standard of construction where prefabrication concept will replace conventional in a target to reduce the dependency on foreign construction labours. To achieve this, the government has encouraged an alternative method of constructing houses known as prefabricated housing. Numerous efforts have been taken by Construction Industry Development Board of Malaysia (CIDB) and other local public and private agencies. However, despite of its various advantages, the uptake of prefabricated housing has been very slow and far behind target. To ensure our housing sector reach its target, there is an urgency for the industry to apply prefabrication. There is a need for government and industry players to know what the obstacles that the industry facing and what steps can be taken to overcome them. This paper aims to discuss the barriers of implementing prefabricated housing and the drivers that can speed up the application. The discussion is based on views from published journals and articles from different stakeholders view such as contractors, developers, clients and prefabrication manufacturers.